Studi Kritis Tujuan, Isi, Metode dan Evaluasi Bahan Ajar PAI Materi (Akidah Akhlak) Kelas I SD IT - Ikbal fatardo; Siti Qomariyah; Ridwan Ridwan; Herdi Herdi; Faisal Hamdi; U. Ruhimatullah (Jurnal Pendidikan Educandum, 2026)
Islamic Education (PAI) at the elementary level is a golden age where the seeds of character are first sown. Within the Integrated Islamic Elementary School (SD IT) environment, the subject of Akidah Akhlak (Faith and Morals) is not merely an additional subject, but the heart of the entire educational process. This research aims to provide a Critical Study Analysis of Islamic Education Teaching Materials regarding Akidah Akhlak for Grade I at SD IT. The study employs a qualitative approach with a descriptive method. This approach was chosen for its suitability in understanding the meaning, processes, and contexts of phenomena as they occur naturally, without experimental treatment. Based on the results of the critical study of the Grade I Akidah Akhlak teaching materials at SD IT, it can be concluded that there is an urgent need for a paradigmatic reconstruction across five primary elements of learning